Analisis Kebijakan Perubahan Kurikulum: Tinjauan Etika Politik Kebijakan Pendidikan Nasional - Umarika Monik Sofi Liana; Sri Minarti (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2026)
Changes to the national curriculum in Indonesia often trigger public cynicism through the slogan "change minister, change curriculum" and create implementation gaps between advanced and remote schools. This study aims to critically analyze the dynamics of this curriculum transition from the perspective of educational political ethics. Using a qualitative, descriptive policy study approach, primary data was collected through in-depth interviews with the Vice Principals for Curriculum at Public Junior High Schools in Bojonegoro Regency. The results show that at the grassroots level, the slogan "change curriculum" is positively deconstructed as a dynamic process of modern improvement. Through asset-based thinking, schools mitigate limited facilities and ethical bureaucratic dilemmas in a humanistic manner through Curriculum Review, Lesson Study, and MGMPS programs. The recommended future curriculum focuses on strengthening practical character and literacy, as well as reinstating the National Examination (UN) as a tool for mapping national quality standards to maintain student learning motivation.